Characteristics of language learning - Kokhan, Olena M. (My University, 2013)
The article deal swith сharacteristics of language learning and the analysis of language learning difficulties is carried out. The special attention is paid to overcoming the language barrier for language learners.
Keywords: вивчення іноземної мови; міжкультурна комунікація; соціальні мережі; мовний бар'єр; language learning; cross-cultural communication; social networking; кафедра іноземних мов професійного спрямування